Eksplorasi desain coffee table dari bonggol jagung dengan optimalisasi teknik bending laminasi - Mahaelani, Shopie Putri; Andry, Andry (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
This research is based on the design of a coffee table that utilizes corn cobs as the main raw material, with a focus on the creative novelty of conventional products. This design is motivated by the opportunities in the bending lamination technique in processing corn cobs. So the purpose of this research is to produce a novel coffee table design using the bending lamination technique. To achieve this goal, the researcher uses a form exploration approach through the design by drawing method based on 3 design stages. This stage begins with the process of understanding the design problem, which begins with an understanding of the material through the experience of directly making a coffee table owned by PT. Matahati Kreasi Nusantara, and ends with the design development stage. At the end of the research, a design was produced in the form of a production drawing of a coffee table in the shape of a third circle, which is integrated with a storage space in the form of a box. Most of the research was conducted at PT. Matahati Kreasi Nusantara, for 1 month. The research resulted in the discovery that corn cob material as a large agricultural industrial waste can be utilized into various products through various techniques to expose the characteristics of corn cobs. One of them is through the bending technique which is the advantage of corn cob material because it is easier to bend compared to other materials.